Novel association of CHEK2 mutation in gastrointestinal stromal tumor: A case report and literature review - Hu, Trevor T; Pazhyattil, Joyce; Richman, Allison M.; Henderson, Kathryn; Groh, Darren; Abdulrahim, Ahmed F. (Human Pathology Reports, 2025)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, typically driven by mutations inc-KITorPDGFRA. TheCHEK2gene encodes a checkpoint kinase involved in DNA damage response and has been implicated in hereditary cancer syndromes. However, its role in GIST pathogenesis remains unexplored.We report the case of a 67-year-old male with recurrent GIST who was found to harbor aCHEK2mutation. The patient initially presented with an abdominal mass, and histopathologic evaluation confirmed a spindle cell neoplasm with strong immunoreactivity for CD117, DOG1, and CD34. Molecular analysis identified a pathogenicCHEK2mutation, a finding not previously described in GIST. The patient was managed with surgical resection following imatinib therapy, with ongoing surveillance for recurrence.The discovery of aCHEK2mutation in GIST raises important questions about its potential role in tumorigenesis and therapeutic response. Given the established involvement ofCHEK2in genomic stability and checkpoint regulation, its presence in GIST warrants further investigation. This case highlights the need to exploreCHEK2mutations in larger cohorts to determine their clinical significance and potential impact on treatment strategies. This case represents the first reported association ofCHEK2mutation with GIST, expanding the known genetic landscape of this tumor. Further studies are necessary to elucidate the implications of this mutation in GIST pathophysiology and treatment.